Neonatal and postneonatal mortality in very low birthweight infants. - Yu, V Y (1984)
We reviewed 388 very low birthweight infants admitted to this neonatal intensive care unit over a four year period to determine the pattern of neonatal and postneonatal deaths up to age 2 years. Neonatal mortality is no longer an adequate indicator of outcome because deaths arising from perinatal events occur after the first month of life.